고려재조대장경의 조성과정 연구 - 송일기 (서지학연구, 0(49), 2011)
이 연구는 고려 재조대장경의 조성주체와 조성과정을 종합적으로 검토한 내용이다. 재조본의 조성에는 중앙에 대장경 조성을 총괄하는 대장도감을 두고 지방에 분사도감을 설치하였으며, 실제적인 판각과 인경 작업에는 당시의 대표적 사원에서 수행하여 성공적으로 완료할 수 있었다. 필자는 이 연구에서 대장경의 조성과정을 구체적으로 조판준비기․경판조판기․경판이운기․불경인출기 등 4단계로 구분하여 살펴본 바, 각 단계 마다 체계적이고도 효율적으로 운영됨으로써 1251년에 전체 공정을 불과 16년 만에 완수할 수 있었던 것으로 파악하였다. 다만 종래 연구에서 권말에 새겨져 있는 ‘造成記’를 ‘刊記’로 이해함으로서 대장도감과 분사도감을 ‘板刻處’로 인식하여 오해를 낳고 있다. 그러나 고려대장경은 국가적 차원에서 조성되었기 때문에 권말에 새겨져 있는 조성기를 사찰본과 같이 간기로 볼 수는 없다는 점을 지적하였다. This research examined comprehensively the process and authorities of making the Goryeo Jaejo-Daejanggyeong(고려재조대장경). To remake Daejanggyeong, Daejangdogam(大藏都監), the central supervisory government office, and Boonsadogam (分司都監), local offices, were established, and the actual operations of engraving and printing were performed in the major temples at that time. Thus the work could be successfully completed. In this research, writer divided the whole process of making Daejanggyeong into 4 specific stages: pre-engraving stage, engraving stage, gathering panel stage, and printing stage. The respective stages were operated so systematically and efficiently that the huge project could be completed in 1251. It took just 16 years to finish. Joseonggi(造成記 writings on making) engraved at the end of it has been misunderstood as Gangi(刊記 writings on printing) in the previous researches. So Daejangdogam and Boonsadogam were also misunderstood as the places of engraving. However this research pointed out that .since the Goryeo Daejanggeong was made nationwide, its Joseonggi cannot be considered as Gangi like the ones in temple versions. KCI Citation Count: 10